Surface electromyography in the assessment of masticatory muscle activity in patients with pain-related temporomandibular disorders: a systematic review - Szyszka-Sommerfeld, Liliana; Sycińska-Dziarnowska, Magdalena; Spagnuolo, Gianrico; Woźniak, Krzysztof (Frontiers in Neurology, 2023)
Background: Temporomandibular disorders (TMD) are a group of orofacial pain conditions that are the most common non-dental pain complaint in the maxillofacial area. The primary symptom of pain-related TMD (TMD-P) is persistent, recurrent or chronic pain involving the muscles of the mandible, the temporomandibular joint (TMJ), and/or adjacent structures. The multifactorial etiology of this condition makes it difficult to provide an precise diagnosis, and valid tools are needed for proper evaluation. One of the useful method that can provide important quantitative data for assessing patients with TMD-P is surface electromyography (sEMG). The aim of this systematic review was to summarize the existing scientific evidence regarding the assessment of masticatory muscle activity (MMA) in patients with TMD-P using sEMG. Methods: A literature search was conducted in electronic databases, such as PubMed, Web of Science, Scopus and Embase using the following keywords: “pain” AND (“temporomandibular disorder*” OR “temporomandibular dysfunction*”) AND “surface electromyography” AND “masticatory muscle activity”. The inclusion criteria were studies assessing MMA in patients with pain-related TMD using sEMG. The Quality Assessment Tool for Quantitative Studies developed by the Effective Public Health Practice Project (EPHPP) was used to assess the quality of the included studies. Results: The search strategy identified 450 potential articles. Fourteen papers met the inclusion criteria. Global quality rating for most of the studies was weak. Most studies showed that the sEMG activity of the temporal anterior (TA) and masseter (MM) muscles at rest in TMD-pain subjects was higher than in the asymptomatic controls, while the MM and TA muscles were less active in the pain-related TMD group compared to the control group during maximal voluntary clenching (MVC). Conclusions: Differences were found in masticatory muscle activity in the TMD-pain population compared to a healthy control group during various tasks. The diagnostic efficacy of sEMG in identifying subjects with TMD-P remains unclear.